Análise de possíveis cenários para utilização de biogás em um frigorífico - Antunes, Marcelo Lourenço (My University, 2019)
The use of biogas in an installation can make it energy independent, as it is a gas with high energy potential, is a renewable source of energy and represents an excellent economic and environmental alternative. This work evaluated possible scenarios for the use of biogas in a swine slaughterhouse, providing different solutions for the use of this highly valued energy input. The scenarios envisioned were: evaluation of the implementation of a biogas combustion system to replace boiler firewood; use of biogas for electricity generation for internal use; and sale of biogas to consumer companies in the market. Using biogas in the boiler can reduce costs and reduce ergonomic risks for the operator. In addition, it was the most attractive option, from an economic point of view, due to the shorter term for recovery invested capital (2.94 years), among the three scenarios evaluated. The use of biogas for electricity generation for internal use has shown that it is possible to improve the availability of electricity in the plant through biogas by acquiring a new generator set. Selling biogas to an outside company for use as a fuel or for producing biomethane may be a good alternative because of the good quality and quantity of biogas generated in the plant. However, this scenario resulted in a longer return on invested capital among the three scenarios assessed (6.45 years). Because the facility's power generation potential exceeds the predicted power consumption by 17.7% in the first two scenarios, it is possible to work with both simultaneously. The financial analysis of this option showed a discounted payback of 3.6 years, being in an intermediate position between the periods of the first and second scenarios.
O uso do biogás em uma instalação pode torná-la energeticamente independente, por ser um gás com alto potencial energético, ser uma fonte renovável de energia e representar uma excelente alternativa econômica e ambiental. Este trabalho avaliou possíveis cenários para utilização de biogás em um frigorífico de suínos, oportunizando diferentes soluções para uso deste insumo energético bastante valorizado. Os cenários vislumbrados foram: avaliação da implementação de um sistema de combustão de biogás para substituição de lenha em caldeira; utilização do biogás para geração de energia elétrica para uso interno; e venda do biogás para empresas consumidoras do mercado. O uso do biogás na caldeira pode reduzir custos e reduzir riscos ergonômicos para o operador. Além disso, foi a opção mais atrativa, sob o ponto de vista econômico, devido ao menor prazo para recuperação do capital investido (2,94 anos), dentre os três cenários avaliados. A utilização do biogás para geração de energia elétrica para uso interno demonstrou que é possível melhorar a disponibilidade de geração de eletricidade na planta através do biogás, pela aquisição de um novo grupo gerador. A venda do biogás para uma empresa externa, para uso como combustível, ou para produção de biometano, pode ser uma boa alternativa pela boa qualidade e quantidade de biogás gerado na planta. Entretanto, esse cenário resultou em um tempo de retorno do capital investido maior dentre os três avaliados (6,45 anos). Devido ao potencial de geração de energia da instalação exceder em 17,7% o consumo de energia previstos nos dois primeiros cenários, é possível trabalhar com ambos, simultaneamente. A análise financeira desta opção, demonstrou um payback descontado de 3,6 anos, ficando em posição intermediária entre os períodos do primeiro e segundo cenários.
Keywords: Biogás; Biocombustíveis; Desenvolvimento energético; Economia - Análise; Biogas; Biomass energy; Energy development; Economics - Analysis